Does the use of a template board imply new normative data for the Jebsen-Taylor Hand Function Test?. (June 2016) - Harte, Daniel; Hamill, Philip; Wilson, Lynn
Introduction: Recent research reports the necessity of a template board to ensure accuracy when administering the Jebsen-Taylor Hand Function Test. However, the original studies that collected normative data did not use a template board. This study collected a sample of data for one female age group of the Jebsen-Taylor Hand Function Test using a template board. Methods: Thirty female participants with no history of hand trauma or a condition affecting the hand were recruited. Each participant carried out subtests 2, 3, 5, 6 and 7 of the Jebsen-Taylor Hand Function Test, which was compared to the normative data available for this test. Results: Results show a significant difference in the mean performance for subtest 2 (non-dominant) and subtest 3 (dominant and non-dominant) with p -values < 0.05 for a difference in means t -test. The remaining subtests 5, 6 and 7 were not statistically significant. Conclusions: The findings reported in this study add to the empirical evidence investigating the normative data for the Jebsen-Taylor Hand Function Test. The statistically significant difference in mean times for two subtests suggests that new normative data may need to be established if clinicians intend to use a template board when administering the test. Resolving this issue is a natural avenue for further research in this area.